Geotextile Filtration Tests on Two Brazilian Soils and Current Filter Criteria. Issue 1 (1st January 1995) - Almeida, M.S.S; Ehrlich, M.; Spada, J.
Abstract : This paper presents results of filtration tests with geotextiles in combination with a uniform fine sand and a clayey fine sand. The tests with the clayey sand were long term tests during which the pH, electrical conductivity and turbidity of the percolation water were monitored with time. These observations, together with a detailed measurement of permeability values, indicate that the three geotextiles performed adequately with regard to drainage and soil particle retention. It is shown that current geotextile filter design criteria are conservative and only one among six criteria was able to predict the behavior of all the geotextiles tested.